HIV and AIDS Risk Reduction Intervention Programmes among in-school Adolescents in Imo State, Nigeria - Ezeama Martina .C; Ezeamah Franklin Ikenna; Enwereji; Ezinna E (Journal of Clinical Research In HIV AIDS And Prevention, 2016)
Introduction: Human Immuno-deficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) constitute public health challenge in Nigeria and adolescents are increasingly becoming vulnerable. It is necessary to provide adolescents in schools with risk-reduction educational interventions so as to expose them on the need to protect themselves from getting infected. This study used risk-reduction interventions (Class-room Instruction and Drama) to encourage risk-reduction practices among in-school adolescents. Materials and Method: Quasi-experimental design using 165 students randomly selected from three convenient co-educational secondary schools in the rural areas was adopted. Two experimental groups, class room instruction (CI) and drama (DR) were used. Baseline data using semi-structured questionnaire with 27- point risk reduction practices were collected. Data were analysed with descriptive statistics, t-test and ANOVA at p =0.05. Result: Scores for HIV risk reduction practices among the adolescents at baseline, classroom instruction (CI), drama (DR) and control respectively were 18.5±4.6, 19.8 ± 5.8 and 17.0 ± 4.8 . The mid-term scores obtained were 23.8 ± 3.4, 23.6 ± 3.4 and 17.7 ± 5.1. The scores obtained for CI, DR and control groups at follow-up were 24.9 ± 2.6, 26.7 ± 1.1 and 17.0 ± 5.3 respectively. The results showed more effective risk reduction practices among the intervention groups than control group. Conclusion Drama intervention yielded more positive outcomes in risk-reduction practices than others. Drama is therefore recommended as the best HIV and AIDS intervention programme for in- school adolescents.
Keywords: HIV/AIDS